Pre-university training: traditions and novations in transformation conditions of higher education - Udovitskaya , T. (New Collegium, 2021)
The article deals with the notion of ‘pre-university training’, its role and significance in young people’s start in professional training in higher education have been considered. Herewith, the role of pre-university training in lowering the risks which arise in this process has been stated. The most typical risks, belonging to the category of social risks, have been considered, their classification has been provided. It has been noted that such risks are objectively determined with a new social environment where young people get into while entering higher educational establishments, also with new forms of learning activities which are often unfamiliar to the current school graduates. The main forms of work with the prospective students in the system of pre-university training have been analysed, their impact on more effective adaptation, first of all of first year students to their learning in a modern higher educational establishment, has been shown. Such analysis has been undertaken based on the experience of Kharkiv University of Humanities ‘People’s Ukrainian Academy’ as for organizational activities of the Pre-University Training Centre during thirty years. The transformation of pre-university training system in conditions of admission changes in higher educational establishments has been considered, namely the increase of educational component in general subjects within the training process for external independent evaluation of education quality.